STUDENT MANAGEMENT IMPLEMENTATION IN FORMING STUDENT CHARACTER - Abdurrahman, Abdurrahman; Syahrullah, Moh (Managere: Indonesian Journal of Educational Management, 2022)
This study aims to analyze the implementation of student management in building student character at school. The research approach is a qualitative descriptive approach with a case study type. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out in stages, starting from data collection, data presentation, data reduction, and concluding. The results showed that the implementation of student management in building student character at Nurul Jadid Middle School was well. From the study results, the implementation of student management in the formation of students at SMP Nurul Jadid has been maximized. This can be seen from the process applied from planning to students graduating from SMP Nurul Jadid.